A Conversation Analysis on Interview with Prime Minister Julia Gillard in Sky News Australia Channel - Eka Yanualifa Telomensi Sitepu; Ridwan Hanafiah; T. Thyrhaya Zein (Yayasan Visi Intan Permata, 2020)
The aims of this research are to identify and analyze how the aspects of conversational interactions are realized in the conversation. In collecting and analyzing the data, the researcher uses documentation method and qualitative content analysis. The utterances which used by the interviewer and interviewees are as the data of this research, while the video of the interview which downloaded from Youtube with 29:44 minutes is as the source of data in this research. The data are analyzed by using Paltridge theory. This research results are, five aspects of conversational interactions are used by the interviewer (Peter Vanillin) such as, Opening Conversation, Adjacency Pairs, Preference Organization, Turn Taking and Closing Conversation, while the interviewer does not use Feedback and Repair. However, five of seven aspects are used by the interviewees (Paul Kelly and Julia Gillard) such as, Adjacency Pairs, Preference Organization, Turn Taking, Feedback and Repair, while the interviewees do not use Opening and Closing Conversation. Thus, all of seven aspects of conversational interactions are used with different realization. The realization of those aspects of conversational interactions used by the interviewer and interviewees are different. The interviewer does not use Feedback and Repair, while the interviewees do not use Opening and Closing Conversation.